(Information sheet) A method of accelerating germination and growth of probiotic spore bacteria - Knysh, Оксана; Martynov, Artur; Skliar, Nadiia (Annals of Mechnikov's Institute, 2024)
Co-cultivation of Heyndrickxia coagulans, Bacillus subtilis, Alkalihalobacillus clausii on nutrient agar with 0.5 % taurine and 1.0 % tomato paste (in terms of the finished medium) leads to a twofold acceleration (from 48 hours to 24 hours) of the appearance of the first colonies (spore germination) and increases the size and number of colonies during cultivation. In addition, the obtained biomass has direct antagonistic properties against the control microorganisms: P. aeruginosa, S. aureus, P. vulgaris, which is explained by the presence of bacteriocins (monocultures of probiotic bacilli do not have such properties). Keywords: Heyndrickxia coagulans, Bacillus subtilis, Alkalihalobacillus clausii, co-cultivation, solid media, taurine, tomato extract, bacteriocins, antagonism.